1997
DOI: 10.1128/iai.65.4.1357-1363.1997
|View full text |Cite
|
Sign up to set email alerts
|

The fibronectin-binding protein of Streptococcus pyogenes, SfbI, is involved in the internalization of group A streptococci by epithelial cells

Abstract: Streptococcus pyogenes organisms (group A streptococci) are considered to be highly adhesive extracellular pathogens. However, it has recently been reported that S. pyogenes has the capacity to efficiently invade eukaryotic cells. In this study, we demonstrate that the interaction of S. pyogenes fibronectin-binding protein (SfbI) with fibronectin on nonphagocytic HEp-2 cells triggers bacterial internalization. Blocking of the SfbI adhesin by either antibodies against the whole protein or antibodies against the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(142 citation statements)
references
References 31 publications
2
140
0
Order By: Relevance
“…This difference is not statistically significant (P ¼ 0.07), but the results could suggest that the reduced virulence of AP1(pPTF8) bacteria in control mice ( Figure 5A) is partially restored in pFn-null mice. As pFn-null mice still express cFn in all tissues and protein F1 can interact with cFn (Ozeri et al, 1996;Molinari et al, 1997), the data support the notion that cFn prevents full restoration of virulence in pFn-null mice.…”
Section: S Pyogenes Bacteria Expressing Protein F1 Are Less Virulentsupporting
confidence: 69%
“…This difference is not statistically significant (P ¼ 0.07), but the results could suggest that the reduced virulence of AP1(pPTF8) bacteria in control mice ( Figure 5A) is partially restored in pFn-null mice. As pFn-null mice still express cFn in all tissues and protein F1 can interact with cFn (Ozeri et al, 1996;Molinari et al, 1997), the data support the notion that cFn prevents full restoration of virulence in pFn-null mice.…”
Section: S Pyogenes Bacteria Expressing Protein F1 Are Less Virulentsupporting
confidence: 69%
“…Interestingly, entry of S. pyogenes has been related to caveola-dependent endocytosis; indeed, it seems to be the major entry route for S. pyogenes (41). In addition, it has been shown that beads coated with the FN-binding protein Sfbl of S. pyogenes are efficiently taken up by cells (30,41). Therefore, we suggest that binding to FN might be a general mechanism for transport of FN-bound viruses, bacteria, and other ligands into cells.…”
Section: Discussionmentioning
confidence: 99%
“…A standard antibiotic protection assay was used for quantification of adherent GAS after 0.5 h, 1 h and 2 h (Molinari et al, 1997). Intracellular bacteria were quantified at time points 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 20 h, 24 h and 48 h p.i.…”
Section: Adherence and Invasion Assaymentioning
confidence: 99%